DAYA MANGSA PREDATOR Harmonia axyridis TERHADAP KUTU DAUN Mizus persicae PADA TANAMAN JERUK - Otto Endarto; Susi Wuryantini (JURNAL AGRONIDA, 2019)
The research aims to determine the prey abilily and preferences of Harmonia axyridisagainst Mizus persicae on citrus. The study was conducted at the screen house and EntomologyLaboratory of the Research Institute for Citrus and Sub-Tropical Fruits, in January-March 2016.The test for prey ability used the first larval stage of H. axyridis to imago for 30 individuals in eacharena. Data were analyzed by counting of M. persicae which eaten per day from each stage, i.e.larva instar, and H. axyridis imago, as well as the average prey during their life cycle. The resultsshowed that the highest prey of H. axyridis occurred in instar larvae 4, which reached 428.3% ofis body weight, with a number of preys 9.81 ± 1.01 head / day. Preferences of H. axyridis in instarslarvae 1,2, and 3 were instar nymphs 1 from M. persicae, and for H. axyridis the instar larvae 4and imago preferred of instar nymph 4. H. axyridis had a life cycle with a range of 6.6 -9.7 days.The duration of egg stage of the H. axyridis was 3 days, the larvae consisted of 4 instars, theduration of the stage for each instar was 2.4 days for instar 1 and 2; 5 days for instar 3; 12 daysfor instar 4, and 18.5 days for imago.Keywords: Prey, predator Harmonia axyridis, Mizus persicae, citrus